Diagnostic value of metagenomic next-generation sequencing in sepsis and bloodstream infection - Qin, Cuihong; Zhang, Shuguang; Zhao, Yingying; Ding, Xianfei; Yang, Fei; Zhao, Yangchao (Frontiers in Cellular and Infection Microbiology, 2023)
Objective: To evaluate the diagnostic value of metagenomic next-generation sequencing (mNGS) in sepsis and bloodstream infection. Methods: A retrospective analysis of patients diagnosed with sepsis and bloodstream infection at the First Affiliated Hospital of Zhengzhou University was conducted. All the patients underwent blood cultures and were divided into mNGS group and non-mNGS group according to whether mNGS was performed or not. The mNGS group was further divided into early group (< 1 day), intermediate group (1-3 days), and late group (> 3 days) according to the time of mNGS inspection. Results: In 194 patients with sepsis and bloodstream infection, the positive rate of mNGS for identifying pathogens was significantly higher than that of blood culture (77.7% vs. 47.9%), and the detection period was shorter (1.41 ± 1.01 days vs. 4.82 ± 0.73 days); the difference was statistically significant (P <0.05). The 28-day mortality rate of the mNGS group (n = 112) was significantly lower than that of the non-mNGS group (n = 82) (47.32% vs. 62.20%, P = 0.043). The total hospitalization time for the mNGS group was longer than that for the non-mNGS group (18 (9, 33) days vs. 13 (6, 23) days, P = 0.005). Sub-group analysis of patients in the mNGS group showed that the total hospitalization time and the ICU hospitalization time in the late group were longer than those in the early group (30 (18, 43) days vs. 10 (6, 26) days, 17 (6, 31) days vs. 6 (2, 10) days), and the ICU hospitalization time in the intermediate group was longer than that in the early group (6 (3, 15) days vs. 6 (2, 10) days); the differences were statistically significant (P <0.05). The 28-day mortality rate of the early group was higher than that of the late group (70.21% vs. 30.00%), and the difference was statistically significant (P = 0.001). Conclusions: mNGS has the advantages of a short detection period and a high positive rate in the diagnosis of pathogens causing bloodstream infection and, eventually, sepsis. Routine blood culture combined with mNGS can significantly reduce the mortality of septic patients with bloodstream infection.